TARJIH AL-SHAWKĀNĪ DALAM TAFSIR FATḤ AL-QADĪR: Studi Penafsiran Surah al-Nūr - Umiatu Rohmah; Tsalis Muttaqin (STAI AL-ANWAR SARANG, 2023)
Differences in interpretation that emerge among mufasir become a very influential factor in understanding the text of the Qur`an, both in terms of creed and sharia law. Therefore, tarjih as a solution to the differences of the opinion becomes a quite important study. One of the scholars who focused on various differences of opinion and conducted tarjih in his exegesis is Imam al-Shawkānī with his book, Tafsir Fatḥal-Qadīr. This research examines al-Shawkānī's interpretation in Tafsir Fatḥal-Qadīr using a descriptive-critical analysis method through literature research. This research aims to describe the model or method of tarjih used by al-Shawkānī in his book, Tafsir Fatḥal-Qadīr, specifically for surah al-Nūr. The problem of this research is limited to thetarjih of the interpretation of Surah al-Nūr using the terms أرجح (arjah), أولى (awla), and الأولى (al-awla). This research uses al-Ḥarbī's tarjih ulumul qur`an approach. The results of the research reveal that al-Shawkānī uses a method of tarjih based on the context of the Qur'an, tarjih using sunnah, tarjih based on the reasons for the descent of the verses, tarjih using qarīnah, and tarjih based on the Arabic language in determining the most valid opinion.